Two novel cell culture models of buccal mucosal oral cancer from patients with no risk-habits of tobacco smoking or chewing. (February 2021) - Vipparthi, Kavya; Patel, Ankit Kumar; Ghosh, Subhashis; Das, Subrata; Das, Chitrarpita; Das, Koyeli; Sarkar, Anwesha; Thatikonda, Venu; Pal, Biswajoy; Remani, Arun Sasi kumaran Nair; Arora, Neeraj; Parihar, Mayur; et al.
Graphical abstract: Highlights: Two cell line models of buccal mucosal oral cancer from patients with no tobacco consumption habits. Germ-line mutation status is considered to make somatic mutation calls, confidently. Both cell lines were distinct in genomic-makeup and in vitro functions. GBC02 3D-cultures may facilitate drug discovery research against cisplatin-refractory oral cancer. Abstract: Objective: Tobacco consumption is one of the major etiological factors for oral cancer, but it also develops in non-tobacco users, with unknown etiologies. Cellular models for tobacco associated oral cancer are available, however; reports of cellular models for studying non-tobacco associated oral cancer are limiting. We report here the establishment and characterization of two novel buccal mucosal cancer cell lines 'GBC02′ and 'GBC035′ derived from non-tobacco users. Materials and methods: Short tandem repeats (STR) profiling, Next-generation sequencing for whole-genome, exome and copy number alterations, immunofluorescence, flow-cytometry, proliferation, live-cell chemotaxis, 3D-spheroid formation, chemotherapy response, gene-expression microarray, gene-set enrichment analysis and xenograft development were performed. Results: Sources of the established cultures were matched to their donors through STR profiling. Genome sequence analysis revealed somatic mutations in TP53, CASP8, CDKN2A for GBC02 with deletions and amplifications encompassing CDKN2A, FAT1 and CCND1, PIK3CA, SOX2, EGFR, MYC genes, respectively. GBC035 harbored mutations in FAT1, NOTCH1, HRAS, CDKN2A, HLA-B, HLA-A genes. While GBC035 cells showed higher E-Cadherin positive cell-cell junctions and collective cell migration in chemotaxis; GBC02 cells were vimentin-positive and demonstrated individual cell migration. Further, exhibiting their relevance to preclinical research, GBC02 3D-spheroids demonstrated enrichment of development-related gene-signatures in microarray transcriptome analysis and were resistant to Cisplatin, but showed sensitivity to cancer stem cells-targeting drug, Salinomycin. Additionally, tumorigenic ability of GBC02 was demonstrated. Conclusions: Altogether, we present here comprehensively characterized unique cell lines established from non-tobacco associated tumors, which may serve as models for preclinical investigations of oral cancers caused independent of tobacco usage.